2010
DOI: 10.1002/app.31654
|View full text |Cite
|
Sign up to set email alerts
|

Thermosensitive PCL‐PEG‐PCL hydrogels: Synthesis, characterization, and delivery of proteins

Abstract: In this work, a biodegradable and injectable in situ gel-forming controlled drug delivery system based on thermosensitive poly(e-caprolactone)-poly(ethylene glycol)-poly(e-caprolactone) (PCL-PEG-PCL) hydrogels was studied. A series of PCL-PEG-PCL triblock copolymers were synthesized and characterized by 1 H-NMR and gel permeation chromatography (GPC). Thermosensitivity of the PCL-PEG-PCL triblock copolymers was tested using the tube inversion method. The in vitro release behaviors of two model proteins, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 28 publications
0
53
0
Order By: Relevance
“…Both PCL-PEG-PCL and PEG-PCL-PEG are biodegradable, and can sustain drug release in an extended period. One could choose to use PCL-PEG-PCL or PEG-PCL-PEG hydrogels according to the practical needs of different applications [107].…”
Section: Pharmaceutical Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Both PCL-PEG-PCL and PEG-PCL-PEG are biodegradable, and can sustain drug release in an extended period. One could choose to use PCL-PEG-PCL or PEG-PCL-PEG hydrogels according to the practical needs of different applications [107].…”
Section: Pharmaceutical Applicationmentioning
confidence: 99%
“…Released HRP was confirmed to preserve its biological activity by specific enzymatic activity assay, in fact gel formation and degradation studies indicated that PCL-PEG-PCL copolymers hydrogels could give a sustained release for at least 45 days by subcutaneous injection. So the great thermosensitivity and biodegradability of these copolymers make them promising gel forming controlled drug delivery system for therapeutic proteins [107].…”
Section: Pharmaceutical Applicationmentioning
confidence: 99%
“…From the spectra of the pure materials, it was apparent that the peak at a chemical shift of around 3.6 ppm is representative of PEO. This peak is attributed to the methylene protons of the -CH2-CH2O-in the PEO chain structure [17]. The other peaks can be attributed to PCL, or in the case of the peak around 7.2 ppm, to both polymers.…”
Section: Blend Compositionsmentioning
confidence: 94%
“…Attempts to increase the stability of poloxamer through the addition of copolymers such as pluronic 25R4 (20), dextran (21), carrageenan (22), and methylcellulose (23) have had limited success. Biodegradable triblock copolymers made up of polycaprolactone (PCL) and polyethyleneglycol (PEG) (i.e., PEG-PCL-PEG, PCL-PEG-PCL) are reported to be stable in aqueous conditions but the crystallinity of the PCL blocks slowed degradation (24)(25)(26). In this study, two novel thermosensitive pentablock copolymers consisting of polyethyleneglycolp o l y c a p r o l a c t o n e -p o l y l a c t i d e -p o l y c a p r o l a c t o n epolyethyleneglycol (PEG-PCL-PLA-PCL-PEG) were studied as injectable hydrogels, with the polylactide (PLA) blocks being added to accelerate the degradation of PCL (27,28).…”
Section: Introductionmentioning
confidence: 99%